2020
DOI: 10.3390/mi11060616
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Properties of Transparent Anatase/Rutile Mixed Phase Glancing Angle Magnetron Sputtered Nano-TiO2 Films

Abstract: Transparent polycrystalline TiO2 thin films have been deposited on unheated glass substrates using RF reactive magnetron sputtering. Depositions were carried out at different glancing angles and with different total gas mixture pressures. The variation of these parameters affected the crystal phase composition and the surface morphology. Depending on the glancing angle and the pressure, rutile, mixed anatase/ rutile and pure anatase were deposited at low substrate temperature. Both hydrophilic and hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…This finding indicates that the established anatase coating could improve the wetting behavior of SLA, which is desirable for cell responses. The results concerning anatase coating-related hydrophilicity agree with the findings of other research groups [44,45]. The results of our previous study have also revealed that a thin coating of the crystalline anatase modification results in a hydrophilic surface [29].…”
Section: Discussionsupporting
confidence: 91%
“…This finding indicates that the established anatase coating could improve the wetting behavior of SLA, which is desirable for cell responses. The results concerning anatase coating-related hydrophilicity agree with the findings of other research groups [44,45]. The results of our previous study have also revealed that a thin coating of the crystalline anatase modification results in a hydrophilic surface [29].…”
Section: Discussionsupporting
confidence: 91%
“…The calculated band gaps are 3.71-3.84 eV and 3.45-3.61 for direct and indirect allowed transitions, respectively, which is higher than the bulk CdS, CuS, and CuCdS 2 . Larger band gaps are usually reported for the amorphous compounds, impurities, defects, or structural disorders, which is in good agreement with XRD and Raman results [46,47]. These factors can also modify the optical band gap and lead to similar values for direct and indirect band gaps [48].…”
Section: Optical Properties By Uv-vis and Fourier-transform Infrared ...supporting
confidence: 83%
“…Wettability, which is a crucial property to determine the contact ability of a liquid on a solid surface, results from the intermolecular interactions of the intrinsic surface energy and surface morphology when the liquid and solid surface are brought together [ 17 , 18 ]. Numerous studies have focused on the control of wettability of real surfaces, which can be divided into hydrophilicity and hydrophobicity according to the contact angle (CA) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%